Social Anti-institutions - Михаил Валентинович Сухарев (Journal of Economic Sociology, 2010)
During the last ten years economists draw more and more attention to the institutional theory; large-scale social-economic changes in the post-soviet countries facilitate this growth of interest. However the practice has shown that general economic theory faces the big difficulties in explanation of the economic phenomena in the societies with the system of informal institutions that considerably differ from the western ones. The paper considers the interaction of formal and informal institutions. With the help of the analysis of the interaction of the rules and techniques the anti-institutions origin is studied. The function of the institutions is described from the ideo-material systems point of view. Finally, the processes of the formalization and takedown of the anti-institutions are under focus.